Penerapan Metode Simpleks untuk Menentukan Keuntungan Maksimum Penjualan Jamu Beras Kencur pada Kelompok Usaha Jamu “Jahe Sribu” - Erny Untari; Indra Puji Astuti; Doni Susanto (LP. Ma'arif Janggan Magetan, 2023)
In the world of trading, optimization problems include maximizing profits (maximization) or minimizing costs (minimization), both of which can be solved using the simplex method. The aim of this research is to maximize the production profits of the Ginger Sribu herbal business group whose address is Bulu Village, Sukomoro District, Magetan Regency using the simplex method. This research was conducted at the Jahe Sribu herbal medicine house (Nur Rohmiati's mother's house) as a production site for Ginger Sribu herbal medicine. The analysis carried out in this research used the simplex method with the Microsoft Excel solver function. The instruments used were observation and interviews. The results of the research show that there is an optimum production amount for each product (small bottle of kencur rice 250ml, medium 500ml, large 600ml) in the production of the Ginger Sribu herbal medicine business group so as to obtain maximum profits.